Kebebasan Murid Thariqah - Nur Aziz Afandi; Mohammad Asy’ari (Jurnal Psikologi Integratif, 2017)
Human according to existential psychology is a free being, with the freedom human can choose and be responsible for his choice. Conversely, if human is not free, he does not feel free and responsible for his choice. That is not human existence. Many attempts made human to exist as a free human. Among these efforts are those carried out by the Sufis by studying tasawwuf. Sufis can reach the condition of a servant's ecstasy to the form of God. Such a condition a Sufi has been freed from everything other than God, he has become independent. This article explains how the experience of freedom of a tariqah murid who studied tasawwuf with the guidance of a murshid more or less for 18 months. Articles are compiled from interviews with a tariqah murid  in Sidoarjo. The results of this study indicate that murid' freedom can be manifested in several conditions or situations when faced with problems, as educators or carers and in situations or conditions of self-development to know oneself